Boosting photocatalytic H2O2 production in pure water over a plasmonic photocatalyst with polyethylenimine modification. Issue 3 (20th December 2022) - Li, Xiangming; Zhu, Junjia; Sun, Bo; Yuan, Qi; Li, Haitao; Ma, Zequn; Xu, Tiwen; Chen, Xingyuan; Fu, Meng
Abstract : A novel TiO2 /PEI/AgNP plasmonic photocatalyst fabricated via electrostatic assembly and in situ polyethylenimine reduction for boosted H2 O2 production is reported. Abstract : Solar-powered photocatalytic H2 O2 production is promising for its advantages of being safe, portable, green and energy efficient but achieving high efficiency is challenging, especially under pure water and air conditions. Herein, a titanium dioxide/polyethylenimine/Ag nanoparticle (abbreviated as TiO2 /PEI/AgNP) photocatalyst is prepared in a facile manner by electrostatic assembly and in situ polymer reduction, which combines local surface plasmon resonance and photocatalysis to exhibit ultra-fast H2 O2 production activity in pure water. The obtained photocatalysts exhibit an unexpectedly high H2 O2 production activity (1605 μmol g −1 h −1 under simulated sunlight) in air and pure water, which is 24-fold higher than that of pristine rutile TiO2 . The TiO2 /PEI/AgNP composites simultaneously optimize three parts of photocatalytic H2 O2 production: (i) improved charge separation, (ii) captured H + faster and (iii) blocked direct contact of H2 O2 and the catalyst. Experimental data and density functional theory calculations prove that the AgNP component can rapidly conduct high-energy electrons generated by themselves and photogenerated electrons generated by TiO2 to reactants. The PEI component can capture H + from pure water faster to promote the superoxide radical to generate H2 O2 through the proton coupling reaction and block direct contact of H2 O2 and the TiO2 component. This work establishes a paradigm for the rational design of efficient plasmonic photocatalysts via self-assembly and in situ reduction technologies toward H2 O2 production in pure water and air.